Alloyable Viscous Fluid for Interface Welding of Garnet Electrolyte to Enable Highly Reversible Fluoride Conversion Solid State Batteries. (23rd November 2022) - Liu, Yangyang; Meng, Junwei; Lei, Meng; Yu, Yifan; Lai, Chuanzhong; Li, Chilin
Abstract: The garnet‐type solid‐state Li‐metal batteries are promising to develop into the high‐energy‐density system when coupled with the high‐capacity conversion reaction cathodes. However, the high interfacial resistance and poor contact between garnet electrolyte and Li anode are still a challenge. Here, an alloyable viscous fluid strategy is proposed for Li/garnet interface welding to enable highly reversible fluoride conversion solid‐state batteries. The super‐assembled phenide polymer with liquid metal property can serve as "oily" interlayer to in situ construct an ionic/electronic mixed conduction network by thermal and electrochemical lithiation. The resultant healing effect of contact voids between garnet and Li enables a dramatic reduction of interfacial resistance to 6 Ω cm 2 . The confinement and compaction of conversion products by garnet electrolyte endow the FeF3 based batteries with long‐cycling and high‐rate performance (520 and 330 mAh g −1 at 0.2 and 2 C respectively). This ceramic configuration also endows the CuF2 conversion battery with much better rechargeability (instead as widely known primary battery). Abstract : An alloyable viscous fluid strategy for Li/garnet interface welding is proposed to enable highly reversible FeF3 and CuF2 conversion solid state batteries, with excellent product confinement and compaction effects. The super‐assembled phenide polymer with liquid metal property can serve as "oily" interlayer to in situ construct ionic/electronic mixed conduction network by thermal and electrochemical lithiation.